Software and Hardware Support of the Project “Library of a New Generation in Creative University” at the Kemerovo State Institute of Culture - E. I. Bobrova (Библиосфера, 2022)
The results of the project “Library of a new generation in creative university” within the framework of the federal project “Creative People”, carried out at the Kemerovo State Institute of Culture in the direction of “Library and information activities” in terms of software and hardware implementation, are presented. Goals and objectives of the project were the following: creation of a comfortable environment for students, organization of an accessible environment for servicing people with disabilities, implantation of RFID systems, digital technologies for the formation of digital competencies of students and improvement of the digital information environment of the institute. The software and hardware, the results of their operation are considered. The practical results of the project implementation are outlined: the introduction of new services on the library bases, promotional events, publications in professional editions, the inclusion of the elective “VR-design” in the curriculum, the formation of digital content (electronic library of music publications, 3D modeling), the transfer of the library fund to RFID technology. Project prospects are shown: experiments in the field of work with information support of science and education, the formation of an open information space, including the work with new types of data; enriching the educational experience of students by creating a rich educational environment in physical and virtual space.